JACKFRUIT SEED AS A NOVEL SUBSTRATE FOR THE PRODUCTION OF AN ACIDOPHILIC AND ACID-STABLE α-AMYLASE FROM BACILLUS SP.4 - TAMRAKAR, BABLEE; KUMARI, KUSUM; KUMARI, PRITI; NAVALE, SHREYA; POKHREL, SUSHIL; NADUMANE, VARALAKSHMI KILINGAR (Innovare Journal of Agricultural Sciences, 2021)
Objective: The objective of the current study is to do a comparative analysis of the ability of a strain of Bacillus to grow and produce α-amylase on various agro-residues under solid state fermentation (SSF), as amylases comprise one of the most important enzymes in industries. Methods: Bacteria were isolated from various soil samples by serial dilution method, screened for amylase production by rapid screening method on starch agar plates and the best amylase producer was chosen. The best isolate was cultured on different agro-residues such as wheat bran, watermelon outer rind, Avarekai seed coat (Dolichos lablab), coconut endosperm, and jackfruit seeds for maximum amylase production. The pH and temperature optima of the enzyme were determined by culturing the bacteria under different pH and temperatures. The crude enzyme was purified by ammonium sulfate precipitation followed by ion-exchange chromatography methods. Results: The best isolate chosen was Bacillus sp.4, which produced an acidophilic and acid-stable α-amylase with maximum enzyme production at the acidic pH of 5.5 and 6.5 (21.11 and 21.62 U/mg protein, respectively) and maximum stability at pH 5.5. Jackfruit seed was found to be the most suitable agro waste for α-amylase production by our isolate. Purification of the enzyme by ammonium sulfate precipitation followed by ion-exchange chromatography resulted in 23.17-fold increase in its activity (86.67 U/mg protein). Conclusion: Considering its acid-stable and highly promising enzyme activities, the enzyme from this bacterial isolate can be further characterized for future applications in starch and other food industries.